Smoking relapse reasons among current smokers with previous cessation experience in Shanghai: A cross-sectional study - Ruiping Wang*; Lingzi Shenfan*; Yu Song*; Qingliang Wang*; Rui Zhang; Le Kuai; Bin Li (Tobacco Induced Diseases)
Introduction Quitting smoking can lead to substantial health gains, even later in life. Many smokers who attempt to quit experience several relapses before achieving sustainable cessation. This study aims to ascertain the differences between quitters with short and long abstinence time and to explore relapse reasons among smokers with cessation experience in Shanghai.